2019
DOI: 10.1186/s12870-019-1784-0
|View full text |Cite
|
Sign up to set email alerts
|

Salicylic acid-induced differential resistance to the Tomato yellow leaf curl virus among resistant and susceptible tomato cultivars

Abstract: Background: In higher plants, salicylic acid (SA) plays important roles in inducing resistance to biotic and abiotic stresses. Tomato yellow leaf curl virus (TYLCV) causes a highly devastating viral disease in plants, particularly in tomato. However, the roles of SA in inducing tomato plant resistance to TYLCV remain unclear. Results: In this study, we investigated whether the exogenous application of SA can improve the resistance of tomato plants to TYLCV in two tomato cultivars, resistant 'Zhefen-702' and su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
1
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(59 citation statements)
references
References 64 publications
3
49
1
6
Order By: Relevance
“…S3). ARF5 [36], TAS14 [37], E4 [38], PR1 [39], WRKY37 [40] and D27 [41] could be induced by IAA, ABA, Ethephon, SA, MeJA and GR24 respectively, while CLAU [42], GA20ox1 [43] and CPD [44] could be repressed by 6-BA, GA 3 and EBL respectively. And expectedly, the expression of these genes under corresponding hormone treatment were basically in line with the reports published before, for example, TAS14 and PR1 were greatly induced over hundreds times by ABA and SA respectively, suggesting the effective treatment of plant hormone.…”
Section: Expression Pro Les Of Slbes1 Genes In Response To Plant Hormonementioning
confidence: 97%
“…S3). ARF5 [36], TAS14 [37], E4 [38], PR1 [39], WRKY37 [40] and D27 [41] could be induced by IAA, ABA, Ethephon, SA, MeJA and GR24 respectively, while CLAU [42], GA20ox1 [43] and CPD [44] could be repressed by 6-BA, GA 3 and EBL respectively. And expectedly, the expression of these genes under corresponding hormone treatment were basically in line with the reports published before, for example, TAS14 and PR1 were greatly induced over hundreds times by ABA and SA respectively, suggesting the effective treatment of plant hormone.…”
Section: Expression Pro Les Of Slbes1 Genes In Response To Plant Hormonementioning
confidence: 97%
“…They were also described the phenomena of SA defense in plant and their useful aspects against the future famines(Zhao et al 2017). Many researchers concluded that the exogenous application of SA induce resistance in host plant against different viral plant pathogen by the accumulation of PR-proteins and by activating the different antiviral gene expression (Li et al 2019;Zhang et al 2020;Wang et al 2019;Patni and Ansari 2019;Koo et al 2020;Jahan et al 2019). The current study also revealed that the exogenous application of botanicals (Eucalyptus and Mint) reduce the disease severity of treated plant before the inoculation of virus.…”
Section: Effect Of Reducing Agents On Virus Longevitymentioning
confidence: 99%
“…Plants respond to oomycete infection by multiple defense mechanisms, including strengthening of physical barriers, production of antimicrobial molecules, and programmed cell death 19 . In addition, many biological and chemical elicitors, such as necrotizing pathogens, salicylic acid (SA), benzothiadiazole (BTH), and methyl jasmonate (MeJA), have been reported to activate plant immune response to pathogens 20 23 . These elicitors cause the induction of a primed state of enhanced defenses which allows plants to display either faster, stronger, or both, activation of the defense responses after further attacks by pathogens or insects, and also under abiotic stress conditions 24 .…”
Section: Introductionmentioning
confidence: 99%